A Neglected Problem: Understanding the Effects of Personal and Vicarious Trauma on African Americans’ Attitudes Toward the Police - Pryce, Daniel K. (Criminal justice and behavior, 2021)
The relationship between the police and African Americans has had a contentious history for decades. To explore this topic further, we interviewed 77 African Americans in the City of Durham, NC, about the declining relationship between their community and the police. We find that African Americans’ perceptions of the police are nuanced and complicated by personal experiences, vicarious experiences of relatives and friends, and news from social media and television regarding policing practices and treatment, including police harassment and/or brutality. We characterize these direct and vicarious experiences as the transmission of trauma. Even for the proportion of African Americans who had positive perceptions and interactions with the police, their views of the police seemed to be further complicated by broader concerns of discriminatory treatment. We proffer solutions to improve the relationship between the police and African Americans. The implications of our findings for future research are also discussed.